The Southern Provinces in bilateral cooperation during the Mahathir and Abdullah years - Khadijah Md Khalid; Loh, Jason Seong Wei (Penerbit Universiti Kebangsaan Malaysia, 2017)
Malaysia’s relations with Thailand can be described as paradoxical. On the one hand, bilateral ties had been the least ‘problematic.’ On the other, the situation in the Southern Provinces had constrained relations and this could be seen during the administrations of Mahathir and Abdullah which became preoccupied with finding solutions. In ‘aggregating’ these two polar states together (‘superposition’), one could construe or amplify bilateral relations within a broader range of so-called overall ‘benign neglect’ that to a certain extent – characterised the approach of successive administrations of both countries. The objective of this paper as conditioned by archival sources as well as interviews seeks, therefore, to highlight the under-appreciated and overlooked role of the leadership factor in bilateral relations. This is in turn co-related to developments in political contestations and reconfigurations centred in Bangkok (“national politics”) which whilst promising little hope on the resolution for peace and stability in the Southern Provinces – contributes to the (unchanging) broader narrative. In short, directions in bilateral relations have been – to a critical extent – determined, influenced and constrained by the inability to achieve a breakthrough to the situation in the Southern Provinces.